Untranslatability in the Book the Subtle Art of Not Giving a Fu*K and Strategies Used to Overcome - Winaria Simanjuntak (CV. ULIL ALBAB CORP, 2024)
This research aims to explore the untranslatability of book The Subtle Art of Not Giving a Fu*k by Mark Manson and its Bahasa Indonesia translation by F. Wicakso and how to overcome them. This research is a descriptive qualitative research which discussed the untranslatability in the book and overcame solutions to each of phenomena. The data in this research is the untranslatable expressions in in the book. The collected data is classified into the types of untranslatability which is proposed by Catford (1965). To overcome untranslatability, this research offers solutions that are proposed by Baker (2018).